Comparison of fluorescence intensity of protoporphyrin IX as observed on the screen of different cystoscopic systems - Hideo Fukuhara; Takahiro Nishimura; Yu Shimojo; Keiji Inoue (Photodiagnosis and Photodynamic Therapy)
Background: Photodynamic diagnosis-assisted transurethral resection of bladder tumor (PDD-TURBT) is an important and useful intervention used for removing non-invasive bladder cancer (NMIBC). Several PDD devices can be used in clinical practice, but few reports have compared them.In this study, we examined the differences in detected fluorescence intensity for each PDD device. Methods: The PDD device was used from OLYMPUS, Richard Wolf, and Karl Storz. Light power and illuminance from endoscope were measured. For each PDD device, fluorescence intensity was measured at 3 cm and 8 cm distance from the protoporphyrin IX (PpIX) phantom to the cystoscope. Results: The variation of excitation light power with observation distance were 35.0 %, 27.0 %, and 28.2 % for OLYMPUS, Richard Wolf, and Karl Storz, respectively. The variation of fluorescence intensity with observation distance were 132.8 %, 120.5 %, and 49.8 % for OLYMPUS, Richard Wolf, and Karl Storz, respectively. Conclusions: PDD devices used in clinical practice show both some performance differences between the PDD systems themselves, and also differences in observed fluorescence intensity.